Integrity monitoring of adhesively bonded joints via an electromechanical impedance-based approach. (September 2018) - Zhuang, Yitao; Kopsaftopoulos, Fotis; Dugnani, Roberto; Chang, Fu-Kuo
Monitoring the bondline integrity of adhesively bonded joints is one of the most critical concerns in the design of aircraft structures to date. Due to the lack of confidence on the integrity of the bondline both during fabrication and service, the industry standards and regulations require assembling the primary airframe structure using the inefficient "black-aluminum" approach, that is, drill holes and use fasteners. Furthermore, state-of-the-art non-destructive evaluation and structural health monitoring approaches are not yet able to provide mature solutions on the issue of bondline integrity monitoring. Therefore, the objective of this work is the introduction and feasibility investigation of a novel bondline integrity monitoring method that is based on the use of piezoelectric sensors embedded inside adhesively bonded joints in order to provide an early detection of bondline degradation. The proposed approach incorporates (1) micro-sensors embedded inside the adhesive layer leaving a minimal footprint on the material, (2) numerical and analytical modeling of the electromechanical impedance of the adhesive bondline, and (3) electromechanical impedance–based diagnostic algorithms for monitoring and assessing the bondline integrity. The experimental validation and assessment of the proposed approach is achieved via the design and fabrication of prototype adhesively bonded lap joints with embedded piezoelectric sensors and a series of mechanical tests under various static and dynamic (fatigue) loading conditions. The obtained results demonstrate the potential of the proposed approach in providing increased confidence on the use of adhesively bonded joints for aerospace structures.